2004
DOI: 10.1088/0031-9155/49/16/024
|View full text |Cite
|
Sign up to set email alerts
|

In vivomammary tumourigenesis in the Sprague–Dawley rat and microdosimetric correlates

Abstract: Standard methods for risk assessments resulting from human exposures to mixed radiation fields in Space consisting of different particle types and energies rely upon quality factors. These are generally defined as a function of linear energy transfer (LET) and are assumed to be proportional to the risk. In this approach, it is further assumed that the risks for single exposures from each of the radiation types add linearly. Although risks of cancer from acute exposures to photon radiations have been measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…RBE values of 27 to 40 were reported for harderian gland tumor incidence in mice exposed to 600-MeV/nucleon Fe ions (30), and an RBE of 10 was reported for mammary tumorigenesis in female rats exposed to 1-GeV/nucleon Fe ions (31). Although TGFb-mediated EMT is not greater after low fluence Fe particles compared to low-LET radiation, could be a factor in the cancer RBE because the fraction of cells receiving dose from particle traversals or associated delta rays) is small compared with the population of daughter cells that exhibit this biological response.…”
Section: Discussionmentioning
confidence: 99%
“…RBE values of 27 to 40 were reported for harderian gland tumor incidence in mice exposed to 600-MeV/nucleon Fe ions (30), and an RBE of 10 was reported for mammary tumorigenesis in female rats exposed to 1-GeV/nucleon Fe ions (31). Although TGFb-mediated EMT is not greater after low fluence Fe particles compared to low-LET radiation, could be a factor in the cancer RBE because the fraction of cells receiving dose from particle traversals or associated delta rays) is small compared with the population of daughter cells that exhibit this biological response.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports (Fry et al, 1985;Alpen et al, 1993;Dicello et al, 2004;Weil et al, 2009Weil et al, , 2014Grahn et al, 1992;Imaoka et al, 2007;Trani et al, 2010;Datta et al, 2013;Illa-Bochaca et al, 2014;Wang et al, 2015) have suggested that HZE particles and neutrons could produce more lethal tumors compared to tumors produced by low LET radiation or background tumors, which is a qualitative difference not accounted for in current risk estimates. Table 3 summarizes these findings from animal studies with HZE particle beams.…”
Section: Tumor Modelmentioning
confidence: 96%
“…There are gaps in knowledge related to space radiation and carcinogenic processes that must be addressed to validate cancer projection models 58 ( Figure 4). Animal studies generally demonstrate that HZE nuclei have a higher carcinogenic effectiveness than low-LET radiation [59][60][61][62] , but RBE values are difficult to quantify because of statistical uncertainties, which in many experiments prevents a conclusion on response at low dose and dose-rates. The large number of radiation types and energies in space precludes an extensive study of tumor types in different strains of mice with different ion/dose regimes.…”
Section: Insights Into the Molecular Mechanisms Of Radiation-induced mentioning
confidence: 99%